n Bydrae tot die kennis van Planococcus citri (Risso) (Homoptera: Pseudococcidae) - Kriegler, P. J (Stellenbosch : Stellenbosch University, 2012)
Tesis (M. Sc. Agric.) -- Universiteit van Stellenbosch, 1954.